2007
DOI: 10.1007/s10682-007-9162-z
|View full text |Cite
|
Sign up to set email alerts
|

Long term oviposition preference and larval performance of Schizomyia macrocapillata (Diptera: Cecidomyiidae) on larger shoots of its host plant Bauhinia brevipes (Fabaceae)

Abstract: The Plant Vigor Hypothesis (PVH) proposes that natural selection on female oviposition choice results from higher fitness of larvae on more vigorous and larger plant modules. For six consecutive years we tested the PVH predictions by investigating the effect of shoot size of Bauhinia brevipes (Fabaceae) on the oviposition preference and offspring survival of the gall-midge Schizomyia macrocapillata (Diptera: Cecidomyiidae). Additionally, we analyzed the effects of bottom-up and top-down mortality forces on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 32 publications
2
46
0
4
Order By: Relevance
“…The effects of habitat fragmentation on populations of gall inducing insects are poorly known (but see Chust et al 2007) and few long-term studies have analyzed gall inducing insect interactions (Santos et al 2008). Studies to date show no consistent response of gall inducing insects to habitat fragmentation; in some cases, gall abundance increases with habitat fragmentation (Wang et al 2005, Chust et al 2007), but in others, no relationship has been found (Julião et al 2004, Dunley 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of habitat fragmentation on populations of gall inducing insects are poorly known (but see Chust et al 2007) and few long-term studies have analyzed gall inducing insect interactions (Santos et al 2008). Studies to date show no consistent response of gall inducing insects to habitat fragmentation; in some cases, gall abundance increases with habitat fragmentation (Wang et al 2005, Chust et al 2007), but in others, no relationship has been found (Julião et al 2004, Dunley 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the mortality factors acting upon the other gall midge, S. macrocapillata, differed significantly from that acting upon A. microcapillata on the same host plant. On S. macrocapillata, an induced resistance mechanism, hypersensitive reaction (a bottom-up effect) accounted for more than 90% of the mortality, making few galls available to be found and killed by natural enemies (Fernandes 1990(Fernandes , 1998Fernandes et al 2000;Santos et al 2008). Pathogenic fungi accounted for no more than 3% as predicted by Fernandes & Price (1992) in xeric environments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on these two galling herbivores showed that S. macrocapillata has a strong preference for longer shoots (Cornelissen et al 1997;Fernandes 1998;Cornelissen & Fernandes 2001, Santos et al 2008 while A. microcapillata lacks a pattern of attack on shoots (Cornelissen et al 1997). In this 3-yr study we tested the preference-performance predictions of PVH that gall induction and survivorship of A. microcapillata are significantly greater on larger shoots and we analyzed the effects of top-down mortality factors on the performance of A. microcapillata.…”
mentioning
confidence: 98%
See 2 more Smart Citations